Թեորեմներ կանոնավոր բազմանկյան դիրքի վերաբերյալ - Առաքելյան, Ռ.
В статье рассматривается задача построения правильного многоугольника, вершины которого расположены в углах бумаги в клетку. Доказываются соответственные теоремы о правильном треугольнике, пятиугольнике и шестиугольнике. Делается обобщение о правильном n - угольнике. The article considers the task of building regular polygon the tips of which are situated in the angles of cross section paper. Homologous theorems on regular triangles, pentagons and hexagons are proved as well. A summary is made concerning a regular polygon having n-angle. It is proved that such a construction is possible for those n-angles sin 360/ n of which is rational number.
Keywords: Մաթեմատիկայի դասավանդման մեթոդիկա